Overseas Chinese Returnees’ Swindler Syndrome and Their Entrepreneurial Education Under Psychological Resilience - Xiao, Can; Wang, Xiaoya (Frontiers in Psychology, 2022)
The study aims to explore the entrepreneurship education of overseas Chinese returnees with the swindler syndrome through psychological resilience. First, a questionnaire survey is conducted to analyze the current situations of entrepreneurship education of overseas Chinses returnees and college students, and it is found that the entrepreneurship education received by overseas Chinese returnees is more advanced and perfect than that by domestic students, which makes overseas Chinese returnees have the ability to solve the problems in the process of entrepreneurship, realizing their entrepreneurial dream. However, the emergence of swindler syndrome changes the self-awareness and psychology of these returnees, which is improved through appropriate entrepreneurship education under resilience analysis. The results show that entrepreneurial resilience and entrepreneurial optimism covered by psychological resilience have a significant positive impact on entrepreneurial intention, indicating that entrepreneurial resilience and entrepreneurial optimism can enhance individual’s entrepreneurial intention. The scores of the subjects with the experience of studying abroad are higher than those without such experience, indicating that overseas Chinese returnees have stronger resilience and more optimistic attitudes in the face of difficulties and setbacks, which provides a new perspective for in-depth analysis of Chinese returnees’ entrepreneurship education and promotes the development of entrepreneurship education in colleges and universities in China.